Nanofibrous poly(lactide-co-glycolide) membranes loaded with diamond nanoparticles as promising substrates for bone tissue engineering - Pařízek, Martin; Douglas, Timothy E L; Novotna, Katarina; Kromka, Alexander; Brady, Mariea A; Renzing, Andrea; Voss, Eske; Jarosova, Marketa; Palatinus, Lukas; Tesarek, Pavel; Ryparova, Pavla; Lisá, Věra; et al. (International journal of nanomedicine, 2012)
BACKGROUND: Nanofibrous scaffolds loaded with bioactive nanoparticles are promising materials for bone tissue engineering. METHODS: In this study, composite nanofibrous membranes containing a copolymer of L-lactide and glycolide (PLGA) and diamond nanoparticles were fabricated by an electrospinning technique. PLGA was dissolved in a mixture of methylene chloride and dimethyl formamide (2:3) at a concentration of 2.3 wt%, and nanodiamond (ND) powder was added at a concentration of 0.7 wt% (about 23 wt% in dry PLGA). RESULTS: In the composite scaffolds, the ND particles were either arranged like beads in the central part of the fibers or formed clusters protruding from the fibers. In the PLGA-ND membranes, the fibers were thicker (diameter 270 ± 9 nm) than in pure PLGA meshes (diameter 218 ± 4 nm), but the areas of pores among these fibers were smaller than in pure PLGA samples (0.46 ± 0.02 μm(2) versus 1.28 ± 0.09 μm(2) in pure PLGA samples). The PLGA-ND membranes showed higher mechanical resistance, as demonstrated by rupture tests of load and deflection of rupture probe at failure. Both types of membranes enabled the attachment, spreading, and subsequent proliferation of human osteoblast-like MG-63 cells to a similar extent, although these values were usually lower than on polystyrene dishes. Nevertheless, the cells on both types of membranes were polygonal or spindle-like in shape, and were distributed homogeneously on the samples. From days 1-7 after seeding, their number rose continuously, and at the end of the experiment, these cells were able to create a confluent layer. At the same time, the cell viability, evaluated by a LIVE/DEAD viability/cytotoxicity kit, ranged from 92% to 97% on both types of membranes. In addition, on PLGA-ND membranes, the cells formed well developed talin-containing focal adhesion plaques. As estimated by the determination of tumor necrosis factor-alpha levels in the culture medium and concentration of intercellular adhesion molecule-1, MG-63 cells, and RAW 264.7 macrophages on these membranes did not show considerable inflammatory activity. CONCLUSION: This study shows that nanofibrous PLGA membranes loaded with diamond nanoparticles have interesting potential for use in bone tissue engineering.
Keywords: Tissue Engineering; Lactic Acid; viabilita buněk; Cell Line; mikrofilamenta; Diamond; testování materiálů; Cell Proliferation; Actin Cytoskeleton; osteoblasty; nanomedicína; Materials Testing; Nanoparticles; nanočástice; Osteoblasts; Cell Survival; diamant; buněčná adheze; tkáňové inženýrství; kostní náhrady; Nanomedicine; kyselina mléčná; Animals; lidé; nanovlákna; Microscopy, Electron, Transmission; Microscopy, Electron, Scanning; Humans; zvířata; Bone Substitutes; Tissue Scaffolds; Nanofibers; myši; buněčné linie; proliferace buněk; tkáňové podpůrné struktury; Polyglycolic Acid; kyselina polyglykolová; Mice; mikroskopie elektronová rastrovací; transmisní elektronová mikroskopie; Cell Adhesion